Role of self-efficacy, outcome expectation, and outcome expectancy in promoting oral health behaviors in adolescent girls - Masoumeh Alidosti; Elahe Tavassoli (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Oral health is a very important issue for different groups, especially adolescents. Social cognitive theory seeks to describe and promote people's health behaviors in a variety of ways. The aim of this study was to determine the role of self-efficacy, outcome expectation, and outcome expectancy in promoting oral health behaviors in adolescent girls in Shahrekord. METHODS: The present study was performed as an intervention in junior high schools in Shahrekord (school year: 2018-2019). Using cluster sampling method, a total of eighty adolescent girls studying in Shahrekord public schools were selected and randomly divided into two groups of intervention and control. A researcher-made questionnaire was used to collect data on demographic variables, outcome expectation, and outcome expectancy constructs. In addition, a checklist was used to assess the status of oral health among the participants. Education for the experimental group was held in four sessions, each lasting 50-60 min. The data required for the study were collected in three stages: before the intervention, immediately after, and 2 months after the intervention. Using SPSS statistical software version 18, the collected data were analyzed through paired t-test and analysis of variance via repeating the observations. RESULTS: There was no significant difference between the two groups in terms of demographic variables. Before the intervention, there was no significant difference between the two groups in terms of the mean scores of outcome expectation, outcome expectancy, and self-efficacy; however, after the intervention, there was an increase in the scores of the experimental group (P < 0.001). Two months after training, there was also a significant increase in the mean score of oral health behavior in the experimental group (P < 0.001). CONCLUSION: Training based on perceived self-efficacy, outcome expectation, and outcome expectancy played an important role in creating the desired attitude toward oral health-promoting behavior among students.